The Implications of Filial Piety in Study Engagement and Study Satisfaction: A Polish-Vietnamese Comparison - Różycka-Tran, Joanna; Jurek, Paweł; Truong, Thi Khanh Ha; Olech, Michał (Frontiers in Psychology, 2021)
Even in psychological literature many determining variables related with school domain are already described, there is no study investigating the universal mechanism underlying parent-child relations, being a prototype matrix for future student-teacher relations. The role of imprinted schema of children’s obligations toward parents seems to be crucial for school functioning in classroom society. The Dual Filial Piety Model (DFPM; Yeh, 2003) is comprised of two higher-order factors that correspond to the two focal filial piety attributes: reciprocal (need of interpersonal relatedness) and authoritarian (need of social belonging and national identity), which have been shown to have distinct implications on social adaptation and individuals’ psychological functioning. In given study, we decide to investigate the relationship between filial piety and study attitudes in more individualistic and egalitarian culture (Poland, N = 310), and more collectivistic and hierarchical society (Vietnam, N = 297). The measurement invariance of three scales i.e. Vietnamese adaptation of DFP Scale, the Utrecht Work Engagement Scale (UWES–S9) and the Study Satisfaction Scale was improved in MLM analyses. Our results show that in more individualistic culture, the RFP (reciprocal mode) is stronger predictor of study engagement and study satisfaction, however the AFP (authoritarian mode) is better factor to predict study engagement in more collectivistic culture. What more, only RFP positively correlates with study satisfaction in individualistic culture. Our findings revealed that in different cultures, different aspects of filial piety should be underlined by parents in context of future academic achievements. The final conclusion is that the prevention and intervention strategies or techniques intended for children with school problems, should be appropriate to culture and addressed in very early stage of education. The results of studies based on the DFPM may stimulate practical applications and policy development in school achievement and failure domain.